Synthetic Approaches to Diospongins: A Two Decade Journey - Tadiparthi, Krishnaji; Chatterjee, Sourav (SynOpen, 2022)
Tetrahydropyran units having multiple stereogenic centers serve as excellent building blocks for various active pharmaceutical ingredients (APIs). In particular, the presence of the unique molecular architecture of the trisubstituted tetrahydropyran (THP) unit in diospongins enhances their biological activity due to multiple stereogenic centers and has attracted attention from the synthetic community over the last two decades. In this review, we discuss synthetic approaches to chiral and racemic forms of diospongins during the period 2006–2020 in chronological order.
Keywords: diospongins; diarylheptanoids; tetrahydropyran; cross-metathesis; hetero-Diels–Alder reaction; asymmetric allylation; enzyme resolution; oxa-Michael addition; Prins cyclization